Development Strategies of Online Sales Sports Products in Iran - Mohammad Saeid Kiani; Leila Nazari; Leila Shahbazpour (Sports Business Journal)
Purpose: Online customers' purchase experience has become significant because of the emergence of the Internet as the primary network for the supply of products and services. The study aimed to introduce critical and influential factors in the progress of online sales of sports products through qualitative and quantitative processes.Methodology: The participants in the qualitative section include 17 managers of sports production companies and sport management experts and sport product consumers. The questionnaire was made through open questionnaires and interviews and weighting of Delphi. And 564 online customers participated in the quantitative section and were analyzed by confirmatory factor analysis.Findings: The findings showed that the components of online retail development include digital strategy, predicting the subsequent purchase of customers, creating value through the marketing mix, providing a dynamic information matrix of goods and equipment, tracking customer-level data, Financial, and information security, website content quality, product and service information evaluation, service tools, and customer value dynamics. As a result, for the development of online retail sales, it is necessary to plan separately for these variables to provide the grounds for the formation of development. Respecting the law of the "chain of businesses" creates an environment rich in interaction and economic synergy, benefiting all aspects of a healthy and dynamic economic puzzle. The dimensions of the development of online retail sales includes digital strategy, predicting the subsequent purchase of customers, creating values through marketing mixes, and evaluating product and service information, service tools, and customer value dynamics.Originality: The study's creativity is to use quantitative and qualitative methods to show the online retail development dimensions of sports goods and equipment.